PERTANGGUNGJAWABAN HUKUM KONSULTASI PELAYANAN KESEHATAN BERBASIS ONLINE - I Gede Perdana Yoga (Fakultas Hukum Universitas Dwijendra, 2018)
ABSTRACT One part of Telemedicine is the existence of an online clinic, where patients and doctors can consult via the internet about the problems of the disease suffered by patients and even doctors can diagnose the patient's condition without having to meet directly and without checking or touching, besides that the patient can also buy medicine directly from the online clinic with advice from a doctor who diagnoses the patient in question, and the delivery of the drug is also done through the express deposit service.The type of research that I use in this study is a type of normative legal research that is looking at and analyzing from the point of view of legislation and the prevailing norms specifically related to the problems in this study. From the discussion and analysis above, it can be concluded that the position of online clinics in terms of health services Judging from existing resources, doctors are the most important resource that plays a role in health services, including internet doctors. The health services are carried out as the implementation of a profession which is the provision of medical assistance based on expertise, skills and precision, which creates legal relations. Referring to the medical practice law, this internet Telemedicine service is not clearly and explicitly recognized as the Health Law, in this Law there is not much explanation in the types of health services or health facilities that are its presence in Indonesia is recognized. Keywords: Health Services, legal liability, online clinics